2019
DOI: 10.5603/aa.2019.0002
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of endostatin, TNF-a VEGFs, MMP-9, and cathepsin-L during three months of diosmin treatment in patients with chronic venous disease (CVD)

Abstract: Introduction: Primary CVD as a result of increased venous hypertension caused mostly by reflux from valvular incompetence as an indication for venoactive drug treatment. The objective of the study was the association between three months of treatment with diosmin and changes to the angiogenic factors involved in the pathophysiology and clinical symptoms of CVD. Material and methods: 41 patients were included in the study. Plasma levels of tumour necrosis factor a (TNF-a), vascular endothelial growth factor (VE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…Prolonged vein wall stretch and wall tension were associated with an increase in HIF-1alpha and MMP-2 and -9 levels and activity, as well as reduced contraction in rat inferior vena cava [23]. The results of our present and previous studies have shown a significant reduction in leg edema, along with a noticeable decrease in HIF-1alpha and MMP-9, cathepsin-L, and endostatin plasma levels at the end of the specific period of diosmin administration [24]. The proinflammatory mediators synthesized at the site of injury, such as TNF-alpha, IL-6, and IL-1beta, further contribute to the expansion of the inflammatory response at the systemic level.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Prolonged vein wall stretch and wall tension were associated with an increase in HIF-1alpha and MMP-2 and -9 levels and activity, as well as reduced contraction in rat inferior vena cava [23]. The results of our present and previous studies have shown a significant reduction in leg edema, along with a noticeable decrease in HIF-1alpha and MMP-9, cathepsin-L, and endostatin plasma levels at the end of the specific period of diosmin administration [24]. The proinflammatory mediators synthesized at the site of injury, such as TNF-alpha, IL-6, and IL-1beta, further contribute to the expansion of the inflammatory response at the systemic level.…”
Section: Discussionsupporting
confidence: 71%
“…IL-6 and IL-1beta have been established to play crucial roles as acute phase reactants and in innate resistance to various inflammatory challenges [ 26 , 27 ]. Based on our recent observations [ 10 , 24 ], prolonged diosmin administration leads to a decrease in inflammatory factors and proteolysis mechanisms associated with the pathogenesis of cardiovascular disease (CVD). This treatment modulates the intensity of inflammatory processes, leading to a reduction in acute-phase cytokine levels and highlighting the role of IL-12 in the chronic phase of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…As indicated by the joint histology results in this and earlier studies, this drop in paw circumference signifies a decrease in swelling rate that can be related to a reduced edema, attenuated inflammatory processes, and reduced hyperplasia of the synovial tissue [ 14 , 15 , 16 , 17 , 18 , 49 ]. These findings could be attributed to the anti-inflammatory actions of diosmin and trolox [ 34 , 50 ].…”
Section: Discussionmentioning
confidence: 99%